Pelatihan Budidaya Jahe dengan Media Karung untuk ketahanan Ekonomi pasca Pandemi Covid-19 di Desa Sumbersih Kecamatan Panggungrejo Kabupaten Blitar - Muhamad Wildan Fawaid; Meta Prila Adelina; Novia Arianti Putri; Yeni Sintya Wati; Habiburohman; Inas Nadifa (LP3M IAIFA Kediri, 2022)
Indonesia nowadays is in a period of adjustment to the new normal after being hit by Covid-19 pandemic which has an impact on various sectors of life, one of which is the economic sector. Each region must have its own potential or advantages, so that in times like these advantages can be used to revive. The one of the region’s potential is that by empowering its human resources , so that they can be used in various empty uses around the house by planting medicinal plants, especially ginger. Ginger is a medicinal plant which contains various benefits, especially for health which can be processed into some products. The method used in this research is Participatory Action Research (PAR) in which this research method observes what is happening in a society at this time. The objectives of this research is to educate the community about the knowledge around ginger, starts from the advantages of ginger until the innovation of ginger planting using sack as the media. The community’s response to this training has been very good and wupports the realization of planting ginger with sack as the media, so it hoped that after this training, the community can use the knowledge that have been given with a proper implementation.